Gastrointestinal Tuberculosis Presenting as Malnutrition and Distal Colonic Bowel Obstruction. (27th February 2018) - Chakinala, Raja Chandra; Farkas, Zahava C.; Barbash, Benjamin; Haq, Khwaja F.; Solanki, Shantanu; Khan, Muhammad Ali; Esses, Edward; Farooq, Taliya; Dworkin, Brad
Abstract : Gastrointestinal (GI) tuberculosis (TB) is rare and can occur in the context of active pulmonary disease or as a primary infection with no pulmonary symptoms. It typically presents with vague abdominal symptoms, making it difficult to discern from alternative disease processes. Although the ileocecal region is the most commonly affected site, tuberculous enteritis can involve any aspect of the GI tract. To demonstrate the importance of maintaining a high clinical suspicion for the disease, we present a case of GI TB presenting as severe malnutrition and segmental colitis of the left colon.